Implementation of the joss (East Java Online Single Submission) Application to Improve Operational Service Efficiency at the East Java Provincial Investment and Integrated One-Stop Service Office - Rosyida, Shofia (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The implementation of information technology in public services is essential to improve the efficiency and quality of government services. The East Java Provincial Investment and Integrated Services Agency (DPMPTSP) has implemented the JOSS (Jatim Online Single Submission) application as a digital system to support the operational processes of licensing and non-licensing services. The purpose of this article is to describe the implementation of the JOSS application and its role in improving the efficiency of operational services within the DPMPTSP of East Java Province. The writing method used is a qualitative descriptive approach with data collection techniques through observation, documentation, and interviews. The results of the analysis show that the implementation of the JOSS application is able to accelerate the service process, improve the accuracy of data management, and facilitate coordination between fields in carrying out operational tasks. In addition, the use of this application also contributes to increasing the transparency and accountability of services to the community. Thus, the implementation of the JOSS (Jatim Online Single Submission) application can be one of the strategic efforts in supporting digital transformation and improving public service performance at the DPMPTSP of East Java Province.